2015
DOI: 10.3402/gha.v8.25756
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an electronic clinical decision support system on workflow in antenatal care: the QUALMAT eCDSS in rural health care facilities in Ghana and Tanzania

Abstract: BackgroundThe implementation of new technology can interrupt established workflows in health care settings. The Quality of Maternal Care (QUALMAT) project has introduced an electronic clinical decision support system (eCDSS) for antenatal care (ANC) and delivery in rural primary health care facilities in Africa.ObjectiveThis study was carried out to investigate the influence of the QUALMAT eCDSS on the workflow of health care workers in rural primary health care facilities in Ghana and Tanzania.DesignA direct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 35 publications
(43 reference statements)
4
61
0
1
Order By: Relevance
“…Furthermore; the HCWs considered that they get guidance for routine questions through using the CDSS where they usually needed colleagues' advice. This is in concordance with the users from Ghana and Tanzania, who also reported that they have learnt by using the CDSS (13,21). In Ghana (13), the HCWs were not asking for information about patients' history before they started to use the CDSS, but started to do so after implementation of the CDSS according to WHO and National health authorities (13).…”
Section: Ojphisupporting
confidence: 54%
See 3 more Smart Citations
“…Furthermore; the HCWs considered that they get guidance for routine questions through using the CDSS where they usually needed colleagues' advice. This is in concordance with the users from Ghana and Tanzania, who also reported that they have learnt by using the CDSS (13,21). In Ghana (13), the HCWs were not asking for information about patients' history before they started to use the CDSS, but started to do so after implementation of the CDSS according to WHO and National health authorities (13).…”
Section: Ojphisupporting
confidence: 54%
“…This creates unwillingness to use the CDSS due to extra efforts this may need. Indeed using the same CDSS, HCWs in Ghana and Tanzania reported that the use of the CDSS multiplied the time spent for ANC by 2.6 in Ghana (going from 7.4 minutes to 19.2 minutes) and 1.7 in Tanzania (going from 15.1 minutes to 25.5 minutes) (13). This is in line with our findings in Burkina Faso where the HCWs reported the time spent for ANC is 15 minutes more with the CDSS.…”
Section: Ojphimentioning
confidence: 99%
See 2 more Smart Citations
“…Details on the aim, development, implementation and costs of the eCDSS are described elsewhere [14,[31][32][33][34][35]. In brief, after a piloting period (including initiation of the eCDSS implementation, testing, translation), the official use of the eCDSS started at the research PHC facilities in November 2012 and was implemented for about 14 months before conducting the post-intervention quality assessment [14,34].…”
Section: Interventions To Improve Quality Of Carementioning
confidence: 99%